International Legal Communication : A Paradigmatic Approach - Joanna Osiejewicz (Routledge, 2026)
This book proposes a new analytical framework for cross-jurisdictional legal communication and analyzes how legal meaning is constructed, negotiated, stabilized, and contested across different institutional and discursive contexts.The text conducts a systematic examination of the communicative structures that underpin legislation, judicial reasoning, legal drafting, advocacy, and transnational legal interaction. It reveals how legal genres, interpretive frameworks, pragmatic assumptions, and discursive strategies fundamentally shape normative effects, institutional authority, and legal legitimacy. Moving beyond conventional approaches that treat communication as supplementary to legal practice, this book demonstrates communication's constitutive role in both the formation and ongoing operation of legal regimes. A pivotal contribution lies in providing a coherent analytical framework that enables readers to identify, compare, and operate effectively within different models of legal communication. This comprehensive framework equips scholars and practitioners with sophisticated conceptual tools for navigating legal complexity, managing interpretive uncertainty, and designing legal communication strategies that enhance accessibility, promote inclusion, and build institutional trust.This book will appeal to scholars and researchers in legal communication, legal linguistics, comparative law, and socio-legal studies.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.